Manajemen Rekrutmen Santri Tahfidz Al-Qu'ran di Ma'had Tahfidz Bina Madani Putri Bogor - Qorni, Agung Wais Al; Mujahidin, Endin (Tawazun: Jurnal Pendidikan Islam, 2021)
The achievement in implementing all programs in the tahfidz al qur'an institution is the result of a combination of neat management, the cleverness of the educators and the availability of facilities and infrastructure as well as the input of quality students, this research finds out how the management of santri Mahad Tahfidz bogor recruitment, a place in meticulous is Ma'had Tahfidz Al-Qur'an Boarding Scool which has a focus and commitment in fostering its students to complete memorization of 30 juz, Ma'had bina Madani Boarding scool which is equivalent to the level of Madrasah aliyah. Research shows the existence of santri recruitment management which is carried out in ma'had bina madani for adequate input attainment in achieving the target of memorizing the Qur'an. This study uses a descriptive qualitative approach with data collection methods with in-depth interviews, observation and documentation. The results showed that ma'had bina madani had managed the recruitment of students which included (1) Planning for Santri Tahfidz (2) Implementation of the New Santri Tahfidz Recruitment which included one PSB committee formation, two determinations of the number of students received, three announcements of new santri admissions. Four Registration Five Entrance Selection Six Announcement of New Santri Admission (3) PSB Evaluation (4) New Student Orientation. Abstrak Ketercapaian dalam melaksanakan semua program dalam lembaga tahfidz al qur'an merupakan hasil dari paduan antara menajemen yang rapih, keiklasan para pendidik dan ktersediaan sarana dan prasarana juga input peserta didik yang berkualitas, peneletian ini mengetahui bagaimana manajemen rekrutmen santri Mahad Tahfidz bogor, tempat yang di teliti merupakan Ma'had Tahfidz Al-Qur'an Boarding Scool yang memiliki fokus dan komitmen dalam membina peserta didik nya untuk menyelesaikan hafalan 30 juz, Ma'had bina Madani Boarding scool yang setara dengan jenjang Madrasah aliyah. Penelitian menunjukan adanya manajemen rekrutmen santri yang dilaksankan di ma'had bina madani untuk Ketecapaian Input yang memadai dalam mencapai target hafalan al quran. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode pengumpulan data dengan wawancara mendalam, observasi dan dokumentasi. Hasil penelitian menunjukan bahwa ma'had bina madani telah melakukan manjemen rekrutmen santri yang meliputi (1) Perencanaan Santri Tahfidz (2) Pelaksanaan Rekrutmen Santri Tahfidz Baru yang Mencakup satu Pembetukan panitia PSB, Dua Penetuan Jumlah Santri yang di terima, tiga Pengumuman Penerimana santri Baru Empat Pendaftaran Lima Seleksi Masuk Enam Pengumuman Penerimaan Santri Baru (3)Evaluasi PSB (4) Orientasi Peserta didik Baru.